High-strength high-thermal-conductivity polyacrylonitrile carbon fiber composite material and preparation method thereof
Through needle-punching stacking and graphitization treatment technology, high-strength and high-thermal conductivity polyacrylonitrile carbon fiber composite materials were prepared, which solved the shortcomings of existing materials in thermal conductivity, electrical conductivity and mechanical properties, and achieved the application in the field of high precision Require.
Patent Information
- Application Number
- CN202411892148.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing carbon fiber composite materials have not yet met the application requirements in the field of high precision in terms of thermal conductivity, electrical conductivity, mechanical properties, etc.
A three-dimensional carbon fiber felt with a Z-oriented structure was laminated by needle-punching, and a reinforced phase was added thereon, followed by a graphitization process to improve the thermal conductivity of the material.
A high-strength and high-thermal conductivity polyacrylonitrile carbon fiber composite material has a thermal conductivity of more than 200W/mK in the vertical direction, a conductivity of more than 1000S/cm, a bending strength of more than 200MPa, and a friction coefficient of less than 0.2.
Smart Images

Figure BDA0005200898760000121 
Figure BDA0005200898760000131 
Figure HDA0005200898770000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal conductive composite materials, and in particular to a high-strength and high-thermal conductive polyacrylonitrile carbon fiber composite material and a preparation method thereof. Background Art
[0002] High-precision and highly integrated electronic components are the inevitable product of economic development. To ensure their safe and efficient operation, it is necessary to quickly channel the accumulated heat. For communication satellites, advanced spacecraft, and probes, efficient heat dissipation is even more essential. During operation, these aerospace equipment not only need to dissipate heat in a timely manner, but also need to maintain an appropriate temperature range to ensure their performance and lifespan.
[0003] In order to ensure the long-term, safe and reliable operation of aerospace equipment, new thermal conductive materials with high thermal conductivity, low thermal expansion rate and low cost have become the top priority of research and development. For new thermal conductive materials, light weight, high thermal conductivity, chemical stability, etc. are basic requirements. In general, carbon fiber composites have a higher degree of matching. At this stage, the preparation of carbon fiber composites generally focuses on the modification of carbon fiber itself, but the thermal conductivity, electrical conductivity, mechanical properties, etc. cannot reach a high value to meet the application requirements in high-precision fields. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a high-strength and high-thermal conductivity polyacrylonitrile carbon fiber composite material and a preparation method thereof, which can effectively solve the above-mentioned problems of the prior art.
[0005] Technical Solution
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0007] The present invention provides a high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material, which is prepared by laminating a single-layer polyacrylonitrile carbon fiber cloth and a single-layer polyacrylonitrile carbon fiber felt in sequence by a needle punching method to form a three-dimensional carbon fiber felt with a Z-directional structure; then a reinforcement phase is added to the three-dimensional carbon fiber felt; finally, a graphitization process is used to treat the carbon fiber felt filled with the reinforcement phase to make it a high-thermal-conductivity polyacrylonitrile carbon fiber composite material with a dense structure.
[0008] Furthermore, the single-layer polyacrylonitrile carbon fiber cloth and the single-layer polyacrylonitrile carbon fiber felt are both prepared by weaving or carding to obtain a planar skeleton structure, and the thickness of the single-layer polyacrylonitrile carbon fiber cloth and the felt are both 0.1-0.5 mm and the density is 100-500 g / m 2 ;
[0009] The acupuncture density is 500-1000 punctures / cm2 The density of the three-dimensional carbon fiber felt is 0.2g / cm 3 Above, thickness is 5-10mm.
[0010] The needling process is mainly to build the Z-direction structure to ensure that the final carbon fiber composite material has 2 or more layers of flat fiber felt or cloth. The needling density is 500-1000 thorns / cm 2 It can be repeatedly needled to control the number of flat fiber felt layers to ensure the density of the fiber felt is 0.2g / cm 3 Above, the thickness is 5-10mm.
[0011] The needling process involves stacking and needling carbon fiber cloth and carbon fiber felt. The carbon fiber felt has a softer texture and can be more closely bonded to the fiber cloth, which can improve interface bonding and thereby improve properties such as thermal conductivity of the composite material.
[0012] Furthermore, after the three-dimensional carbon fiber felt is laser cleaned, the reinforcing phase is added; the laser cleaning parameters are as follows: laser scanning speed is 0-30 mm / s, laser pulse width is 0-350 ns, laser power is 0-100%, and laser frequency is 0-2000 kHz.
[0013] In order to enhance the deposition of the subsequent enhanced phase, laser cleaning is used for pretreatment to increase the surface roughness. Laser cleaning is a green and environmentally friendly treatment method. Compared with sandblasting and sandpaper polishing, it has higher efficiency. The laser scanning speed (0-30mm / s), laser pulse width (0-350ns), laser power (0-100%), laser frequency (0-2000kHz) of the laser cleaning machine can be adjusted to achieve the best cleaning effect.
[0014] Furthermore, the reinforcing phase is added to the three-dimensional carbon fiber felt by using a pressure difference method or a chemical vapor deposition method.
[0015] Furthermore, the reinforcing phase is infused into the three-dimensional carbon fiber felt by a pressure difference preparation method, and then hot-pressed and cured before being graphitized at high temperature; compared with the introduction of carbon sources in other structures, a lower carbon source can be introduced to achieve the same density.
[0016] The pressure difference preparation method is specifically operated as follows: the three-dimensional carbon fiber felt and resin are placed in an autoclave, and the resin quickly penetrates the fiber structure under high pressure heating conditions to eliminate bubbles and enhance the bonding force between the fiber and the resin. The impregnation pressure is 4-7MPa, the impregnation process time is usually 2-4h, and the impregnation temperature is 60-80℃.
[0017] The hot pressing curing adopts ultrasonic heating curing, and the specific operation is as follows:
[0018] The resin composite material to be cured is placed in the ultrasonic heating equipment. The high-frequency vibration of the ultrasonic wave not only helps the resin to be more evenly distributed between the fibers, but also effectively removes bubbles and improves the density of the composite material. The curing temperature is generally controlled at 80-120°C and the curing time is 4-6 hours. This heating method can achieve fast and uniform heating, and can complete the curing reaction at a lower temperature, reducing energy consumption and processing time.
[0019] Furthermore, the reinforcing phase is deposited into a three-dimensional carbon fiber felt by chemical vapor deposition, and then graphitized at high temperature.
[0020] The chemical vapor deposition preparation method is specifically operated as follows: methane (CH4), ethylene (C2H4), propane (C3H8) and other gases are selected as carbon sources. The laser-cleaned polyacrylonitrile carbon fiber composite material is placed in a CVD reactor, and the carbon source gas and hydrogen are introduced by controlling the temperature of the reaction chamber (500-1500°C), and the flow rate is adjusted by a gas flow controller (the gas flow rate is 10-100sccm). The vacuum degree in the chamber is maintained at 10 -3 The carbon source gas decomposes under high temperature conditions and carbon atoms are deposited on the surface of polyacrylonitrile carbon fibers. The deposition time is usually 0-24h, which is adjusted according to the film thickness requirements. High-quality carbon sources can be introduced by precisely controlling temperature, gas flow and pressure.
[0021] Furthermore, the temperature range of the graphitization treatment process is 2800°C and above; the heating rate is 20-40°C / min; and the cooling rate is 20-40°C / min.
[0022] Preferably, the graphitization treatment process adopts step-by-step insulation and extends the insulation time. The slower heating process and insulation time can give the material a longer crystallization and structural adjustment time at high temperature, which is beneficial to reduce lattice defects and improve the thermal conductivity of the material; slow cooling or segmented cooling is adopted to avoid excessive stress inside the material, thereby maintaining its structural integrity and further improving thermal conductivity. Specifically, the step-by-step insulation temperature and insulation time are 1000-1500℃, 2-4h; 1800-2200℃, 4-8h; 2200-2800℃, 8-12h; above 2800℃, 8-12h. The segmented cooling temperature and insulation time are 2200-2800℃, 4-8h; 1800-2200℃, 2-4h; 1000-1500℃, 2-4h; 500-800℃, 1-2h.
[0023] Furthermore, the reinforcing phase is one or both of carbon material and phenolic resin, which can give the carbon-carbon composite material better impact resistance, thermal stability, etc.
[0024] Preferably, the reinforcing phase is made of carbon material and phenolic resin in a weight ratio of 3:1-1:1. The carbon material is graphite.
[0025] Furthermore, the thermal conductivity of the carbon fiber composite material in the vertical and parallel directions exceeds 200 W / mK and 500 W / mK respectively, the electrical conductivity is greater than 1000 S / cm, the bending strength is greater than 200 MPa, and the friction coefficient is less than 0.2.
[0026] A method for preparing a high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material comprises the following steps:
[0027] S1: A single layer of polyacrylonitrile carbon fiber cloth and a single layer of polyacrylonitrile carbon fiber felt are sequentially laminated by needle punching to prepare a three-dimensional carbon fiber felt with a Z-direction structure;
[0028] S2: adding reinforcement phase to the three-dimensional carbon fiber mat;
[0029] S3: The carbon fiber felt filled with the reinforcement phase is treated by graphitization process to make it a high thermal conductivity polyacrylonitrile carbon fiber composite material with a dense structure.
[0030] Preferably, steps S2-S3 are repeated 1-5 times. Most preferably, steps S2-S3 are repeated 3 times.
[0031] Beneficial Effects
[0032] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:
[0033] (1) The present invention first uses a weaving process combined with an airflow combing process to prepare a single-layer planar skeleton structure of polyacrylonitrile carbon fiber felt and carbon fiber cloth; then, the single-layer polyacrylonitrile carbon fiber felt and the single-layer polyacrylonitrile carbon fiber cloth are laminated and composited by acupuncture to prepare a three-dimensional carbon fiber structure with a Z-direction structure; then, a pressure difference method or chemical vapor deposition is used to add a reinforcing phase to the carbon fiber felt or to the fiber; finally, a graphitization process is used to treat the carbon fiber felt filled with the reinforcing phase to make it a high thermal conductivity carbon fiber composite material with a dense structure. The thermal conductivity of the prepared carbon fiber composite material in the vertical direction exceeds 200W / mK, the electrical conductivity exceeds 1000S / cm, the bending strength exceeds 100MPa, and the friction coefficient is less than 0.2.
[0034] (2) The weaving process of the three-dimensional preform has been optimized, which can more effectively improve the structural strength of the material and the fiber content in the vertical direction, thereby greatly improving the thermal conductivity of the carbon / carbon composite material in the vertical direction;
[0035] (3) The present invention uses laser cleaning for pretreatment to increase the roughness of the carbon fiber surface to facilitate the subsequent deposition and attachment of carbon. Laser cleaning is a green and environmentally friendly treatment method and has higher efficiency than sandblasting, sandpaper polishing, etc.
[0036] (4) The present invention utilizes a mixed needle punching method of carbon fiber cloth and carbon fiber felt to increase the tightness between layers. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 The figure is a schematic diagram of the preparation process of the high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] The present invention will be further described below in conjunction with the embodiments.
[0041] The raw material models and manufacturers used in the embodiments and comparative examples are as follows:
[0042] Both polyacrylonitrile carbon fiber cloth and polyacrylonitrile carbon fiber felt use polyacrylonitrile carbon fiber as raw material. The manufacturer of polyacrylonitrile carbon fiber is Japan Toray Corporation, and the model is M60J.
[0043] Phenolic resin: The manufacturer is Jinan Shengquan Co., Ltd., model number is PF7303.
[0044] (I) Embodiment
[0045] Embodiment 1:
[0046] A high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material and a preparation method thereof, the preparation process is as follows Figure 1 As shown, the following steps are included:
[0047] (1) First, polyacrylonitrile carbon fiber was used as raw material, and polyacrylonitrile carbon fiber cloth and polyacrylonitrile carbon fiber felt with a planar skeleton structure were prepared by weaving (PAN-based carbon fiber was plain woven into a mesh structure by a weaving machine. During the weaving process, the fibers were interwoven in the longitudinal and transverse directions to form a stable mesh structure) and combing (the kinetic energy of the airflow was used to distribute the PAN-based carbon fiber in a certain direction to form a uniform fiber layer). The thickness of the formed polyacrylonitrile carbon fiber cloth and polyacrylonitrile carbon fiber felt were both 100 μm and the density was 100 g / m 2 ;
[0048] Then, the polyacrylonitrile carbon fiber cloth and the polyacrylonitrile carbon fiber felt are laminated by needle punching to prepare a complete 3D fiber felt with Z direction; wherein the needle punching density is finally 1000 thorns / cm 2 The thickness of the obtained three-dimensional polyacrylonitrile carbon fiber structure is 10 mm and the density is 0.30 g / cm 3 ;
[0049] (2) pre-treating the 3D fiber felt prepared in step (1) at a laser scanning speed of 30 mm / s, a laser pulse width of 350 ns, a laser power of 100%, and a laser frequency of 2000 kHz to facilitate the subsequent introduction of a carbon source;
[0050] (3) placing the 3D fiber felt treated by laser in step (2) into an autoclave, and injecting the phenolic resin solution into the fiber felt at a high pressure of 7 MPa, with the impregnation temperature and time being 80° C. and 4 h; then placing the 3D fiber felt / phenolic composite material into an ultrasonic heating device for ultrasonic curing, with the curing temperature being 120° C. and the curing time being 6 h, to facilitate the subsequent graphitization step;
[0051] (4) The 3D fiber felt / phenolic composite material in step (3) is placed in a graphitization furnace for graphitization treatment. The graphitization temperature is 3000°C, the heating rate is 20°C / min, and the step insulation temperature and time are: 1200°C, 4h; 2200°C, 8h; 2800°C, 12h; 3000°C, 12h; the cooling rate is 20°C / min, and the segmented cooling temperature and insulation time are 2500°C, 8h; 1800°C, 4h; 1000°C, 4h; 500°C, 1h.
[0052] (5) Repeat steps (3) and (4) three times to obtain a density of 1.8 g / cm 3 of carbon / carbon composites.
[0053] Embodiment 2:
[0054] A high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material and a preparation method thereof, which is different from Example 1 in that steps (3) and (4) are repeated 5 times, and the density of the prepared polyacrylonitrile carbon fiber composite material is 2.0 g / cm 3 .
[0055] Embodiment 3:
[0056] A high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material and a preparation method thereof, which is different from Example 1 only in that step (3) is different. Step (3) is specifically as follows:
[0057] The 3D fiber felt / carbon composite material was prepared by chemical vapor deposition, in which propane (C3H8) was used as the carbon source, the reaction chamber temperature was 1500°C, the gas flow rate was 100 sccm, and the vacuum degree in the chamber was maintained at 10 -4 , the deposition time is 24h.
[0058] The density of the polyacrylonitrile carbon fiber composite material prepared by using Example 3 is 2.0 g / cm 3 .
[0059] Comparative Example 1:
[0060] A high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material and a preparation method thereof, which is different from Example 1 only in that step (4) is different, as follows:
[0061] The 3D fiber felt / phenolic composite material in step (3) is placed in a graphitization furnace for graphitization treatment. The graphitization temperature is 2300°C, the heating rate is 20°C / min, and the step insulation temperature and time are: 1200°C, 4h; 2300°C, 8h; the segmented cooling temperature and insulation time are 2000°C, 8h; 1500°C, 4h; 1000°C, 4h; 500°C, 1h.
[0062] Comparative Example 2:
[0063] A high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material and a preparation method thereof, which is different from Example 1 only in that step (4) is different, as follows:
[0064] The 3D fiber felt / phenolic composite material in step (3) was placed in a graphitization furnace for graphitization treatment, the graphitization temperature was 2300°C, the constant temperature time was 8h, and the heating rate was 20°C / min. No step-by-step heating, heat preservation and segmented cooling treatment was performed, and the furnace was directly cooled.
[0065] Comparative Example 3:
[0066] A high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material and a preparation method thereof, which is different from Example 1 only in that: the reinforcing phase uses graphite and phenolic resin, and the weight ratio is 3:1.
[0067] Comparative Example 4:
[0068] A high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material and a preparation method thereof, which is different from Example 1 only in that: the reinforcing phase uses graphite and phenolic resin, and the weight ratio is 1:1.
[0069] Comparative Example 5:
[0070] A high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material and a preparation method thereof, which is different from Example 1 only in that: step (1) is different, and polyacrylonitrile carbon fiber cloth is used throughout, specifically:
[0071] (1) First, polyacrylonitrile carbon fiber is used as raw material to prepare polyacrylonitrile carbon fiber cloth with a planar skeleton structure. The thickness of the formed polyacrylonitrile carbon fiber cloth is 100 μm and the density is 100 g / m 2 ;
[0072] Then, the polyacrylonitrile carbon fiber cloth is laminated by needle punching to prepare a complete 3D fiber mat with Z direction; wherein the final needle punching density is 1000 thorns / cm 2 The thickness of the obtained three-dimensional polyacrylonitrile carbon fiber structure is 10 mm.
[0073] Comparative Example 6:
[0074] The only difference from Example 1 is that: step (1) is different, all polyacrylonitrile carbon fiber felt is used, specifically:
[0075] (1) First, polyacrylonitrile carbon fiber is used as raw material to prepare polyacrylonitrile carbon fiber felt with a planar skeleton structure. The thickness of the formed polyacrylonitrile carbon fiber felt is 100 μm and the density is 100 g / m 2 ;
[0076] Then, the polyacrylonitrile carbon fiber felt is laminated by needle punching to prepare a complete 3D fiber felt with Z direction; wherein the final needle punching density is 1000 thorns / cm 2 The thickness of the obtained three-dimensional polyacrylonitrile carbon fiber structure is 10 mm.
[0077] Comparative Example 7:
[0078] The only difference from Example 1 is that step (1) is different, specifically:
[0079] (1) First, polyacrylonitrile carbon fiber was used as raw material, and polyacrylonitrile carbon fiber cloth and polyacrylonitrile carbon fiber felt with a planar skeleton structure were prepared by weaving (PAN-based carbon fiber was plain woven into a mesh structure by a weaving machine. During the weaving process, the fibers were interwoven in the longitudinal and transverse directions to form a stable mesh structure) and combing (the kinetic energy of the airflow was used to distribute the PAN-based carbon fiber in a certain direction to form a uniform fiber layer). The thickness of the formed polyacrylonitrile carbon fiber cloth and polyacrylonitrile carbon fiber felt were both 100 μm and the density was 100 g / m 2 ;
[0080] Then, the polyacrylonitrile carbon fiber cloth and the polyacrylonitrile carbon fiber felt are laminated to prepare a 3D fiber felt; the thickness of the prepared three-dimensional polyacrylonitrile carbon fiber structure is 10 mm.
[0081] Comparative Example 8:
[0082] The only difference from Example 1 is that step (2) is missing.
[0083] Comparative Example 9:
[0084] The only difference from Example 1 is that viscose-based carbon fiber is used as the raw material instead of polyacrylonitrile carbon fiber.
[0085] Comparative Example 10:
[0086] The only difference from Example 1 is that the reinforcement phase is only graphite.
[0087] Comparative Example 11:
[0088] The only difference from Example 1 is that the PAN-based carbon fiber felt is pretreated by sandblasting at a pressure of 0.2 MPa and a spray distance of 300 mm instead of laser cleaning.
[0089] (II) Performance test
[0090] (1) Test method
[0091] Conductivity: The volume resistivity and conductivity of carbon fiber composites are tested using a four-probe tester. The four metal probes of the four-probe tester are arranged in a straight line, with one probe acting as a current source, another probe acting as a voltage measurement electrode, and the other two probes used to measure current and voltage. During the measurement process, the probes are placed on the surface of the carbon fiber composite and current is applied.
[0092] Thermal conductivity: The thermal conductivity of carbon fiber composite materials is mainly obtained by multiplying the thermal diffusivity, specific heat and density. The thermal diffusivity is obtained by testing with a laser thermal conductivity meter, the model and manufacturer of which are LFA 467 and NETZSCH of Germany; the specific heat is measured by a differential scanning calorimeter in a nitrogen environment at a heating rate of 10°C per minute, the model and manufacturer of the differential scanning calorimeter are DSC 214 and NETZSCH of Germany; the density is measured by a densimeter, the model and manufacturer of the densimeter are SJ-300G and Shanghai Shuju Instrument Technology Co., Ltd.
[0093] Bending strength: A CMT6103 electronic universal testing machine produced by MTS Industrial Systems was used as the testing equipment.
[0094] Friction coefficient: The friction coefficient of carbon fiber composite materials at room temperature was tested using a reciprocating friction and wear tester. The model of the reciprocating friction and wear tester is GF-1, the manufacturer is Lanzhou Zhongke Kaihua Technology Development Co., Ltd., the applied friction force is 20N, and the friction rate is 500rpm.
[0095] (2) Test results
[0096]
[0097]
[0098] It can be seen from Examples 1-3 that the carbon fiber composite material prepared by the technical solution of the present invention has thermal conductivities exceeding 200 W / mK and 500 W / mK in the vertical and parallel directions respectively, an electrical conductivity greater than 1000 S / cm, a bending strength greater than 200 MPa, and a friction coefficient less than 0.2.
[0099] Combining Example 1 with Comparative Examples 1-2, it can be seen that by adopting step-by-step heating and step-by-step cooling, the thermal conductivity and electrical conductivity of carbon fiber composite materials can be effectively improved; and combining Example 1 with Comparative Examples 5-7, it can be seen that the carbon fiber composite material prepared by laminating and needle-punching polyacrylonitrile carbon fiber cloth and polyacrylonitrile carbon fiber felt has greatly improved thermal conductivity and electrical conductivity. Combining Example 1 with Comparative Example 8, it can be seen that the thermal conductivity and electrical conductivity of the carbon fiber composite material prepared without laser treatment will be affected. Combining Example 1 with Comparative Example 11, it can be seen that laser pretreatment is better than sandblasting or manual polishing. Combining Example 1 with Comparative Examples 3-4 and 10, it can be seen that the use of carbon material as a synergistic reinforcement phase can improve the thermal conductivity and electrical conductivity of carbon fiber composite materials. Combining Example 1 with Comparative Example 9, it can be seen that the composite material prepared using PAN-based carbon fiber is better than viscose-based carbon fiber composite material.
[0100] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material, characterized in that: A single layer of polyacrylonitrile carbon fiber cloth and a single layer of polyacrylonitrile carbon fiber felt are stacked in sequence by needle punching to prepare a three-dimensional carbon fiber felt with a Z-directional structure; a reinforcing phase is then added to the three-dimensional carbon fiber felt; and finally, the carbon fiber felt filled with the reinforcing phase is treated by a graphitization process to make it a high thermal conductivity polyacrylonitrile carbon fiber composite material with a dense structure.
2. The high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material according to claim 1, characterized in that: The single-layer polyacrylonitrile carbon fiber cloth and the single-layer polyacrylonitrile carbon fiber felt are both prepared by weaving or carding to obtain a planar skeleton structure; The acupuncture density is 500-1000 punctures / cm 2 The density of the three-dimensional carbon fiber felt is 0.2g / cm 3 Above, thickness is 5-10mm.
3. The high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material according to claim 1, characterized in that: After laser cleaning the three-dimensional carbon fiber felt, the reinforcing phase is added; the laser cleaning parameters are as follows: laser scanning speed is 0-30mm / s, laser pulse width is 0-350ns, laser power is 0-100%, and laser frequency is 0-2000kHz.
4. The high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material according to claim 1, characterized in that: The reinforcing phase is added to the three-dimensional carbon fiber felt by using a pressure difference method or a chemical vapor deposition method.
5. The high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material according to claim 4, characterized in that: The reinforcing phase is infused into the three-dimensional carbon fiber felt by a pressure difference preparation method, and then hot-pressed and cured and then graphitized at high temperature; The pressure difference preparation method is specifically operated as follows: the three-dimensional carbon fiber felt and resin are placed in an autoclave, and the resin quickly penetrates the fiber structure under high pressure heating conditions to eliminate bubbles and enhance the bonding force between the fiber and the resin, wherein the impregnation pressure is 4-7MPa, the impregnation process time is usually 2-4h, and the impregnation temperature is 60-80°C; The hot pressing curing adopts ultrasonic heating curing, and the specific operation is as follows: placing the resin composite material to be cured in an ultrasonic heating device, the curing temperature is 80-120° C., and the curing time is 4-6 hours.
6. The high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material according to claim 4, characterized in that: The reinforcing phase is deposited into a three-dimensional carbon fiber felt by chemical vapor deposition, and then graphitized at high temperature; The specific operation method of the chemical vapor deposition is as follows: the laser-cleaned polyacrylonitrile carbon fiber composite material is placed in a CVD reactor, the temperature of the reaction chamber is controlled between 500-1500°C, carbon source gas and hydrogen are introduced, and the gas flow rate is adjusted to 10-100 sccm by a gas flow controller, and the vacuum degree in the chamber is maintained at 10 -3 And below, the carbon source gas decomposes under high temperature conditions, and carbon atoms are deposited on the surface of polyacrylonitrile carbon fiber, and the deposition time is 0-24h.
7. A high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material according to claim 5 or 6, characterized in that: The temperature range of the graphitization treatment process is 2800°C and above; the heating rate is 20-40°C / min; the cooling rate is 20-40°C / min; The step-type insulation temperature and insulation time are 1000-1500℃, 2-4h; 1800-2200℃, 4-8h; 2200-2800℃, 8-12h; above 2800℃, 8-12h; The staged cooling temperature and holding time are 2200-2800℃, 4-8h; 1800-2200℃, 2-4h; 1000-1500℃, 2-4h; 500-800℃, 1-2h.
8. The high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material according to claim 1, characterized in that: The reinforcing phase is one or both of carbon material and phenolic resin.
9. The high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material according to claim 1, characterized in that: The carbon fiber composite material has thermal conductivity coefficients exceeding 200 W / mK and 500 W / mK in the vertical and parallel directions respectively, an electrical conductivity greater than 1000 S / cm, a bending strength greater than 200 MPa, and a friction coefficient less than 0.
2.
10. A method for preparing a high-strength and high-thermal-conductivity polyacrylonitrile carbon fiber composite material according to any one of claims 1 to 9, characterized in that: It includes the following steps: S1: A single layer of polyacrylonitrile carbon fiber cloth and a single layer of polyacrylonitrile carbon fiber felt are sequentially laminated by needle punching to prepare a three-dimensional carbon fiber felt with a Z-direction structure; S2: adding reinforcement phase to the three-dimensional carbon fiber mat; S3: The carbon fiber felt filled with the reinforcement phase is treated by graphitization process to make it a high thermal conductivity polyacrylonitrile carbon fiber composite material with a dense structure.
Citation Information
Patent Citations
Carbon fiber composite laser cleaning and surface modified composite processing device and method
CN110586579A
Vanadium dioxide nano carbon fiber composite material, preparation method and application thereof
CN112233911A
Liquid phase-vapor deposition carbon fiber / carbon composite thermal field material and preparation method thereof
CN113896561A